Study on factors that people return to take drugs again after getting well from treatment: https://doi.org/10.69692/SUJMRD090144 - LILIANOU, Lisatteur; PHANALASY, Oudone; SOUKSOMVANG, Phoui; XAYXANADASY, Kedtysack; BOUNPHONE, Khammai; SILIVANH, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The research is the study of factors that make drug addicts return to drugs after treatment well, which has three purposes as follows: (1) study of the drug addicts in treatment centers, then return to drugs again; (2) study the cause of chemotherapy drug addicts, then return to drugs again; (3) rank and order the importance of internal factors and external factors of which makes drug addicts that treat well, then come back to drugs again. The method of this study was using questionnaires to interview people who had been treated well and then returned to drugs at the drug treatment center in Vientiane Capital and some villages. The total number of interviewees in this study is 355 interviewees. The Analytic Hierarchy Process (AHP) is applied to this study. From the study, there are 294 males and 61 females out of 355 interviewees; the oldest is between 25-30 years old and the youngest is under 12 years old. Almost interviewees are single; the occupations of drug addicts are mostly laborers and unemployed people; the income of most drug addicts has non-regular income; the most drugs were amphetamines, cough syrups, marijuana and heroin, respectively. The key people who influence to addiction drugs are friends. Mostly, the addictive drugs used to treat are 2 and 3 times. The causes of the addiction of most interviewees are due to social conditions and lack of self-awareness; in the future, the number of drug addicts will increase even more; the solution for the drug problem in the past has so far failed because there are so many people have involved or government officials behind the drug trade; the factors that make people addicted to drugs and then return to drugs again come from not being able to cut ties with former friends who are addicted to drugs. The percentage of people who have been treated that come back to addict again is between 25% to 50%. Ranking from high to low of the 8 internal factors causing the former drug addicts to come back to the drug again are factors of attitude towards drugs, family aspects, knowledge about the drug in family and of themselves, living experience, parent education, and so on, respectively, and the rank of external factors are other people, social, penalty to retailers and drug addicts, resistance and prevention of families and organizations, trading within communities, economy, environment, and so on.